Fostering sustainable energy transitions in South Africa: a system dynamics approach to achieving a sustainable electricity sector - Du Plooy, Nicole Tina (Stellenbosch : Stellenbosch University, 2017)
Thesis (MEng)--Stellenbosch University, 2017.